A novel potential application of SiC ceramic foam material to distillation: foam monolithic tray. (2nd October 2015) - Gao, Xin; Li, Xingang; Liu, Xia; Li, Hong; Yang, Zhenming; Zhang, Jinsong
Abstract: Applications using foam material as distillation packing or trays have demonstrated higher performance than classical mass transfer units, except for the operation range (Leveque et al., 2009; Zhang et al., 2012 ). To overcome this disadvantage, a series of novel mass transfer units based on foam material has been developed, such as Foam Monolithic Tray, Structured Corrugation Foam Packing and so on. In this article, the hydrodynamic performances and mass transfer efficiency of a SiC foam monolithic tray is examined, with special emphasis on the effect of the foam cell size and tray thickness. The hydraulic performance parameters and the mass transfer efficiency of the foam monolithic tray are measured as 600 mm i.d. and 300 mm i.d. diameter, respectively. The experimental values are compared with the latest trends in distillation trays and traditional column trays. In general, the comparison results indicate that the hydrodynamics and mass transfer performances of the foam monolithic tray meet the requirements for the mass transfer elements in the distillation column. The results also indicate that the foam monolithic tray has higher operation flexibility and significantly reduces the capital cost at the industrial scale. Graphical abstract: Highlights: We developed a novel tray made of SiC foam material for distillation column. The characteristics were measured to estimate the Foam Monolithic Tray. We did a series of comparisons for evaluating the Foam Monolithic Tray. Foam Monolithic Tray is a potential candidate for distillation column.